Rodents and insectivores from the Lower Miocene (Agenian and Ramblian) of the Tudela Formation (Ebro Basin, Spain) - Ruiz-Sánchez, F. Javier; Murelaga, X.; Freudenthal, M.; Larrasoaña, J. C.; Furió, M.; Garcés, M.; González-Pardos, M.; Suárez-Hernando, O. (Journal of Iberian Geology, 2012)
The rodent and insectivore faunas of Agenian and Ramblian age from the Tudela Formation (Ebro Basin, Spain) are described. Four of the localities (CH1, CA1, CC1 and CA2) contain rodent remains of Agenian age (local zone Y), and three (CA3, CA3B and CA4) of Ramblian age (local zones Z and A). Typical Agenian taxa include Armantomys cf. bijmai (CH1), Eucricetodon cf. gerandianus (CA1), Peridyromys turbatus, Simplomys aff. aljaphi and Armantomys daamsi (CA2) and Eucricetodon aff. aquitanicus (CC1). On the other hand, some typical Ramblian taxa are Armantomys cf. parsani (CA3), Ligerimys aff. magnus and Pseudotheridomys sp. (CA4) and Prodryomys cf. brailloni (CA3B). The faunas are characterized by the richness and diversity of the glirids. The presence of the glirid Altomiramys in CA4 represents the first Upper Ramblian record of this taxon.